PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, SISTEM PENGENDALIAN INTERNAL PEMERINTAH, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS PENGELOLAANKEUANGAN DAERAH (Studi Empiris Pada Satuan Kerja perangkat Daerah Kota Dumai) - Siti Hajar; Yusralaini Yusralaini; Lila Anggaraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to exmine the effect of the implementation of financial accounting system, goverment internal control system, and competence human resources of the effectiveness of financial management area in Dumai City. The sampling method used in this study is nonprobability sampling method. Respondent of this study is head of departement, chief financial officer, and treasurer of departement. The sample used of this study were 102 respondents. Data analyzed in this study is multiple linear regression analysis with SPSS. The result shows that: 1) the implementation of financial accounting system area have positive effect on the effectiveness of financial management area with thitung (6,476) > ttabel (1,984) and significance (0000)> 0.05, 2) goverment internal control system have positive effect on the effectiveness of financial management area with thitung (5,733)> ttabel (1,984) and significance (0000) > 0.05, 3) human resources competence have positive effect on the effectiveness of financial management area with thitung (3,385)> ttabel (1,984) and significance (0001) < 0.05. The magnitude of effect (R2 ) the implementation of financial accounting system, goverment internal control system, and competence human resources of the effectiveness of financial management area was 82.5%.Keywords : system, competence, human resources, financial management, goverment and effectiveness